2005
DOI: 10.1002/ddr.20010
|View full text |Cite
|
Sign up to set email alerts
|

Development of colon-targeted albendazole-β-cyclodextrin-complex drug delivery systems

Abstract: Albendazole, a drug for the treatment of gastrointestinal nematode infection, is variably and erratically absorbed from the gastrointestinal tract after oral administration. The present study was aimed at developing matrix tablets of albendazole using guar gum as carrier for colon targeting in order to provide an effective and safe therapy for helminthiasis. To improve its bioavailability, the formation of inclusion complexes of albendazole with b-cyclodextrins was investigated. Matrix tablets of albendazole-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The methods that have been reported for evaluation of colon targeted delivery systems include triggering by enzymes (Philip et al, 2008;Fetzner et al, 2004;Macfarlane et al, 1989;Maculotti et al, 2009;Maestrelli et al, 2008;Liu et al, 2012;Semde et al, 2000a,b Omar et al, 2007Jain et al, 2007a,b et al, 2010), rat caecal contents (Rubinstein et al, 1993;Jain et al, 2007a,b;Watanabe et al, 1998;Takemura et al, 2000;Tiwari et al, 2011;Shukla et al, 2012Shukla et al, , 2011Krishnaiah et al, 2001;Shyale et al, 2005;Ravi et al, 2008;Varshosaz et al, 2010;Singhal et al, 2011;Wei et al, 2007;Seal and Mathers, 2001), human faecal slurries (Salunkhe and Kulkarni, 2008;Siew et al, 2000Siew et al, , 2004McConnel et al, 2007;Karrout et al, 2009;Krenzlin et al, 2011), and multi stage compound culture system (Yang, 2008;Kotla et al, 2014;Schacht et al, 1996). Despite a large number of research reports on microbially triggered delivery systems for colon delivery, no such product is commercially available.…”
Section: Introductionmentioning
confidence: 96%
“…The methods that have been reported for evaluation of colon targeted delivery systems include triggering by enzymes (Philip et al, 2008;Fetzner et al, 2004;Macfarlane et al, 1989;Maculotti et al, 2009;Maestrelli et al, 2008;Liu et al, 2012;Semde et al, 2000a,b Omar et al, 2007Jain et al, 2007a,b et al, 2010), rat caecal contents (Rubinstein et al, 1993;Jain et al, 2007a,b;Watanabe et al, 1998;Takemura et al, 2000;Tiwari et al, 2011;Shukla et al, 2012Shukla et al, , 2011Krishnaiah et al, 2001;Shyale et al, 2005;Ravi et al, 2008;Varshosaz et al, 2010;Singhal et al, 2011;Wei et al, 2007;Seal and Mathers, 2001), human faecal slurries (Salunkhe and Kulkarni, 2008;Siew et al, 2000Siew et al, , 2004McConnel et al, 2007;Karrout et al, 2009;Krenzlin et al, 2011), and multi stage compound culture system (Yang, 2008;Kotla et al, 2014;Schacht et al, 1996). Despite a large number of research reports on microbially triggered delivery systems for colon delivery, no such product is commercially available.…”
Section: Introductionmentioning
confidence: 96%
“…It is clear from these results that MT7 and MT10 formulations could target budesonide to the colon and may be considered as potential formulations for targeting of budesonide to the colon, especially because human caecal contents would be greater than that used in the present study (Shyale et al, 2005). MT10500 which was selected for in vivo studies showed a significant decrease in macroscopic and histological damage scores and colon wet weight/length ratio.…”
Section: Discussionmentioning
confidence: 69%
“…Shyale et al (2005) have also reported in their studies on guar gum, that 7-day enzyme induction was suitable for preparing rat caecal contents with enough concentration of the required enzymes. The rats were then sacrificed by decapitation and after midline incision; luminal contents of caecum and colon were removed and transferred to appropriate buffer solutions containing 0.5% sodium lauryl sulphate (SLS) to preserve the sink condition for budesonide.…”
mentioning
confidence: 87%